Synthesis and electrical characterization of dyesensitized solar cell with Fluorescein Sodium Salt - Farooq, W.A.; Fatehmulla, Amanullah; Yakuphanoğlu, Fahrettin; Yahia, I.S. (My University, 2012)
Fluorescein Sodium Salt dye sensitized solar cell based on nanostructure TiO2 was synthesized. Photovoltaic and impedance spectroscopy properties of the solar cell with fluorescein sodium were investigated. The solar cell gives a short circuit current density of 72?A/cm2 and an open circuit voltage of 0.56 V under AM 1.5. The capacitance-voltage, the conductancevoltage, the series resistance-voltage characteristics of the solar cell were carried out in a wide range of frequency for the development of the dye sensitized solar cells. The present investigation is useful for the improvement of the photovoltaic performance of the solar cell and can be further improved using combination of different dyes. © 2012 IEEE.
2012 9th International Conference on High Capacity Optical Networks and Enabling Technologies, HONET 2012 -- 14 December 2012 through 14 December 2012 -- Istanbul -- 95760
Keywords: Fluorescein Sodium Salt; impedance spectroscopy; Photovoltaic properties; TiO2 nanostructure